2014
DOI: 10.4236/jssm.2014.71001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Leadership Style on the Learning Motivation of Students in Elementary Schools

Abstract: This major objective of this study is to investigate the effect of leadership styles of science teachers on the learning motivation of elementary school students. It is generally known that students' learning motivation could affect the learning achievement. Besides, students with strong learning motivation generally lead to better learning performance. If a teacher can break through the tradition and adopt a creative leadership style, it is possible to increase the learning motivation and result in better lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…pointed out attitudes toward learning as learners' positive or negative emotion, evaluation, and approval or opposed tendency toward learned contents. Lin & Chuang (2014) referred attitudes toward learning to students' methods, motivation, and attitudes engaging in learning activities, including learning methods, skills, and learning habits. Nguyen (2012) further pointed out the premise of good attitudes toward learning as the common realization of teachers and students to the value of teaching and learning; otherwise, the teaching effect would not be fulfilled.…”
Section: Attitudes Toward Learningmentioning
confidence: 99%
“…pointed out attitudes toward learning as learners' positive or negative emotion, evaluation, and approval or opposed tendency toward learned contents. Lin & Chuang (2014) referred attitudes toward learning to students' methods, motivation, and attitudes engaging in learning activities, including learning methods, skills, and learning habits. Nguyen (2012) further pointed out the premise of good attitudes toward learning as the common realization of teachers and students to the value of teaching and learning; otherwise, the teaching effect would not be fulfilled.…”
Section: Attitudes Toward Learningmentioning
confidence: 99%
“…He has proven that only transformative leadership has a favorable relationship with the extra effort of its followers, their effectiveness, and their job and leadership satisfaction. Lin and Chuang (2014) conducted a study to investigate the effects of different leadership styles on the levels of student learning motivation in elementary schools. They found that primary school teachers used a combination of transactional and transformative leadership styles in their classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Motivasyon, bireyin arzu ve isteğini tetikleyerek bir amaç doğrultusunda bireyi harekete geçiren ve belirlenmiş hedeflere yönelik davranışlarını ortaya çıkaran, kontrol eden ve sürdüren psikolojik bir eylemdir (Lin ve Chuang, 2014). Motivasyon dinamik bir kavram olmakla birlikte bireysel hedeflerin yoğunluğunu, yönünü ve örgütsel hedeflere ulaşma çabalarının sürekliliğini açıklayan süreç olarak tanımlanmaktadır (Robbins, Judge ve Vohra, 2014).…”
Section: Motivasyonunclassified